Uterine prolapse with endometrial eversion in association with an unusual diffuse, polypoid, fibrosing perimetritis and parametritis in a cat. Issue 1 (28th January 2016) - Valentine, Matthew J; Porter, Susan; Chapwanya, Aspinas; Callanan, John J
Case summary: This case describes a young non-pregnant cat that presented with uterine prolapse in association with an unusual diffuse, polypoid, fibrosing perimetritis and parametritis. Following ovariohysterectomy the cat recovered fully. No intra-abdominal complications were seen on ultrasound examination 3 months postsurgery. At the time of writing, the cat remains healthy. Relevance and novel information: Uterine prolapse in the cat is relatively rare and usually associated with the periparturient period. Inflammatory polypoid perimetritis and parametritis have not previously been documented in cats, and in dogs have only been reported in association with the administration of oestrogenic compounds. The polypoid inflammation affecting the uterus and parametrium may have contributed to increased laxity of the uterine ligaments and predisposed to the development of uterine prolapse.